N′-(2,5-Dihydroxybenzylidene)benzenesulfonohydrazide - Ali, Hapipah M. (International Union of Crystallography, 2008)
In the title compound, C(13)H(12)N(2)O(4)S, the dihedral angle between the two aromatic rings is 89.5 (1)°. In the crystal structure, molecules are linked by O—H⋯O(hydroxy) and N—H⋯O(sulfonyl) hydrogen bonds, forming a ribbon that propagates along the b axis; there is also an intramolecular O—H⋯N hydrogen bond.